WHICH ONE IS MORE IMPORTANT: INTERNAL CONTROL SYSTEM OR FINANCIAL REPORT ACCESSIBILITY? - Budiarto, Dekeng Setyo; Zulaika, Isnaini Nur (Widya Mandala Surabaya Catholic University, 2022)
Research Purposes. This study aims to examine whether the internal control system and the accessibility of financial reports affect the accountability of village financial management. In addition, this study also analyzes the effect of village financial management accountability on fraud prevention.Research Method. Data were obtained by distributing 152 questionnaires directly (offline) to 38 villages in Sleman Regency. The data is processed using Structural Equation Model (SEM) with Smart-PLS.Research Result and Findings. The results showed that the internal control system and the accessibility of financial reports affected the accountability of village financial management. In addition, village financial management accountability affects fraud prevention. The research implies that the village government can improve supervision and transparency so that the community believes that village funds are appropriately.